2012
DOI: 10.1016/j.celrep.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for a Reciprocal Regulation between SCF and CSN

Abstract: Summary SCF (Skp1-Cul1-Fboxes) E3 ligases are activated by ligation to the ubiquitin-like protein Nedd8, which is reversed by the deneddylating Cop9 Signalosome (CSN). However, CSN also promotes SCF substrate turnover through unknown mechanisms. Through biochemical and electron microscopy analyses, we determined molecular models of CSN complexes with SCFSkp2/Cks1 and SCFFbw7 and found that CSN occludes both SCF functional sites – the catalytic Rbx1-Cul1 C-terminal domain and the substrate receptor. Indeed, CSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
238
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(250 citation statements)
references
References 62 publications
(101 reference statements)
12
238
0
Order By: Relevance
“…As expanded on below, however, the available data indicate that the CRL is unlikely to be in this basal state for a substantial amount of time and, in principle, will probably populate a wide range of architectures during its lifetime. Relevant events that modify the CRL architecture include: activation through the process of neddylation; association of the active neddylated form with the COP9 signalosome (CSN) complex, a multisubunit deneddylase that can sterically block substrate access, catalyse cullin deneddylation, and remain bound to the CRL; loss of SR through proteolytic degradation; and SR exchange via a CAND1-driven mechanism [21,[34][35][36][37][38][40][41][42][43]. A confounding factor to understanding this regulation is that in cells these different events are generally not synchronized for CRLs en masse, or for individual CRL SR complexes.…”
Section: Overview Of Crl Regulatory Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…As expanded on below, however, the available data indicate that the CRL is unlikely to be in this basal state for a substantial amount of time and, in principle, will probably populate a wide range of architectures during its lifetime. Relevant events that modify the CRL architecture include: activation through the process of neddylation; association of the active neddylated form with the COP9 signalosome (CSN) complex, a multisubunit deneddylase that can sterically block substrate access, catalyse cullin deneddylation, and remain bound to the CRL; loss of SR through proteolytic degradation; and SR exchange via a CAND1-driven mechanism [21,[34][35][36][37][38][40][41][42][43]. A confounding factor to understanding this regulation is that in cells these different events are generally not synchronized for CRLs en masse, or for individual CRL SR complexes.…”
Section: Overview Of Crl Regulatory Machinerymentioning
confidence: 99%
“…Nonetheless, the data indicate a second signal could dictate the timing of NEDD8 removal from the cullin [36]. One caveat is that these studies have generally relied on epitope-tagged CSN subunits that might be capable of interacting with CRLs but lack enzymatic activity due to incomplete assembly with the CSN5 catalytic subunit.Third, the association of CSN with potentially active (neddylated and receptor loaded) CRLs renders these complexes functionally inactive and, in essence, removes this population of CRLs from the active cellular pool [40,41]. Biochemical studies, however, indicate that the association of CSN with CRLs can be reversed by the presence of substrates [40,41].…”
mentioning
confidence: 99%
“…Furthermore, the CSN appears to contain two dominant subcomplexes, CSN1/2/3/8 and CSN 4/5/6/7 (37), which correspond to the large and the small segments, respectively, in an EM study of the CSN alone (apo-CSN) (36). An EM study of the CSN in complex with an Skp1-Cul1-Fbox (SCF) E3 ligase was also reported, showing reciprocal regulation between CSN and SCF (38). To date, unfortunately, there is no high-resolution mapping on these subunit interactions.…”
mentioning
confidence: 99%
“…The important findings that the FboxPSkp1 complex can remove tightly bound Cand1 from Cul1, and indication of a transient complex of Cand1 with fully assembled SCF led to proposal of a model for SCF dynamics driven by substrate demand (Figure 1). A key feature of the model is based on recent evidence that substrate binding to CRLs can significantly reduce CSN access and CRL deneddylation [8,9]. When substrates are exhausted, accelerated deneddylation shifts the active SCF complex into a deneddylated transition state, which can either bind new substrate and become reactivated by Nedd8 conjugation, or enter the exchange state.…”
mentioning
confidence: 99%